3(2X^2 + 6X +3) = 6X^2 + 18X + 9 This is the quadratic equation aX^2 + bX + C Where X is the unknown variable to be resolved, and a,b,c are constants Soluttion: X 1,2 3(2X^2...
3(2X^2 + 6X +3) = 6X^2 + 18X + 9 This is the quadratic equation aX^2 + bX + C Where X is the unknown variable to be resolved, and a,b,c are constants Soluttion: X 1,2 3(2X^2...
A Summary of my tutoring methods - I am not the class teacher or the instructor. Tutoring is not the same as teaching a class. This is the main reasons why good tutoring must be done one-on-one. That is, the full attention of the Tutor is on this one student (Tutee) and vice versa. - I am patient with the student and make sure that he/she knows and understand that I am here to help and... read more
Set the following: A = number of apples Sally brought home P = number of plums Sally brought home Sally returned home with two times the number of plums than apples. So: P = 2A Cost of each apple = 50 cents...
Why negative of a negative is a positive ( " – ( – Number ) = + Number" ), and why the use of parenthesis matters in mathematical expressions? A None-Mathematical approach for those of you who are still confused. There are more than few explanations and theories for the mathematical operation “negative –-> negative is positive” or: " – ( – Number ) = + Number"... read more
Comments Regarding the Importance of Learning and Understanding History - The road to WWII. I love History and I know it well. In K-12 we studied history from Ancient times up to the modern history of the 1960’s. In College, I chose American, European and World History as part of my elective non-engineering subjects. My years in Electronic Engineering helped me to sharpen my analytical... read more
We need to find the length of each side of a triangle based on given ratio between the sides and the total length (perimeter) of the triangle given in ft. We can define a triangle ABC with 3 sides a b c. Let side a be the shortest side. (a = shortest side) Let side b be the middle...
Set the following: Length = L Width = W The length is twice the width: L = 2*W or: W = L/2 Perimeter: P = 60ft = 2*L + 2*W Substituting L for W in the perimeter equation gives: P = 60ft = 2*L + 2*(L/2)...
5x-3 < 7 5x < 7+3 5x < 10 x < 2 2-x < x+6 -x - x < 6-2 -2x < 4 multiplying both sides of the equation by -1 gives: 2x < -4 x < -2